Influence of relative age effects and quality of tactical behaviour in the performance of youth soccer players - Costa, I. T. da; Garganta, J.; Greco, P. J.; Mesquita, I.; Seabra, A. (International Journal of Performance Analysis in Sport, 2010)
The present study examines the associations between tactical performance indexes with quality of tactical behaviours and birth-date quarters of youth Soccer players. The sample comprised a total of 534 youth players classified into four seasons of 3 months (January-March; April-June; July-September; October-December). A system of tactical assessment in Soccer (FUT-SAT) was used to collect data. Descriptive statistics and multinomial logistic regression were applied. The tactical performance indexes were divided into tercis (low, moderate and high) in order to evaluate the influences of relative age effects and quality of tactical behaviours. The quality in the "penetration" and "offensive coverage" principles were positively related to moderate performance indexes. Players with the highest quality in the "depth mobility" and "unity defensive" principles were more likely to present higher performance indexes. Regarding the defensive phase, those with better qualities in the "delay","concentration" and "defensive unity" principles were more likely to have moderate performance index. Additionally, better quality in the "defensive coverage" and "balance" principles corresponded to a higher likelihood of having a superior performance index. Relative age effects were observed only in high defensive performance index. The present results revealed a positive correlation between tactical performance indexes and quality of tactical behaviours.